Antitumor activity in advanced cancer patients with thymic malignancies enrolled in early clinical drug development programs (Phase I trials) at Gustave Roussy. Issue 3 (September 2015) - Kossai, M.; Duchemann, B.; Boutros, C.; Caramella, C.; Hollebecque, A.; Angevin, E.; Gazzah, A.; Bahleda, R.; Ileana, E.; Massard, C.; Vielh, P.; Soria, J.C.; et al.
Highlights Thymic malignancies represent a rare disease associated with poor prognosis. When refractory at standard treatments, only few therapeutic options are available. Herein are the outcomes of 22 patients with advanced disease, in Phase I trials. The use of mTOR inhibitors and anti-angiogenic agents showed promising results.